Levonorgestrel Intrauterine System (MIRENA): Initial Experience in the Management of Abnormal Uterine Bleeding - BC, Durga (Journal of Nepalgunj Medical College, 2022)
Introduction: The Levonorgestrel intrauterine system (MIRENA) is a long acting contraceptive device act by releasing progesterone into the uterus It is also efficient in medical management of abnormal uterine bleeding. Levonorgestrel intrauterine system is best option for those ladies who want to avoid surgery in cases of abnormal uterine bleeding. Aims: To assess the effectiveness of MIRENA in abnormal uterine bleeding. Methods: This is a hospital based cross sectional study done at the department of obstetrics and gynecology in ladies with history of abnormal uterine bleeding. The study was done from January 2020 to January 2022 for a period of two years. Data were collected, recorded in standard Proforma and analyzed by using EESPPS version 17. Results: Majority of patients were multipara of age group 35-40 yrs. Mirena caused decrease in heavy menstrual blood loss by 2.4% in 4month of use and 47.6% by one year. After one year of use 83.3% patient had better compliance, 9.5% had expulsion, and only 7.1% had to undergo hysterectomy. Conclusion: Mirena is the best alternative in the medical management of abnormal uterine bleeding with good patient compliance reducing the rate of hysterectomy.